Sandwich-like PdO/CeO2 nanosheet@HZSM-5 membrane hybrid composite for methane combustion: self-redispersion, sintering-resistance and oxygen, water-tolerance. Issue 18 (22nd April 2016) - Dai, Qiguang; Bai, Shuxing; Lou, Yang; Wang, Xingyi; Guo, Yun; Lu, Guanzhong
Abstract : PdO/CeO2 nanosheets@HZSM-5 membrane were prepared via a facile in situ hydrothermal growth process as an efficient catalyst for methane combustion and exhibited outstanding sintering-resistance and oxygen, water-tolerance. Abstract : PdO/CeO2 nanosheets encapsulated by a monolayer of a continuous and dense HZSM-5 zeolite membrane were prepared by a facile in situ hydrothermal growth process and used as a highly efficient and thermally stable catalyst for methane combustion. Uncoated PdO/CeO2 suffered severe sintering at high temperature or high oxygen concentration. However, the encapsulation of HZSM-5 significantly improved sintering resistance by the suppressing effects of the HZSM-5 coating for the agglomeration of PdO x nanoparticles, resulting in the outstanding thermal stability of PdO/CeO2 . Furthermore, the synthesized hybrid materials also exhibited good oxygen- and water-tolerance for methane combustion due to the oxygen or water barrier. In addition, a reactivation behavior was observed due to the self-redispersion of PdO x on CeO2 nanosheets in the reaction atmosphere at high temperature.